Eco Innovación y Tecnología en el Sector de la Energía en la República Dominicana (2020)
The energy for the development and growth of any country plays an important role, while first-hand input to achieve the transformation of goods and services in the world today. Based on the findings in the 1992 Rio Summit the world echoed the need for a significant change in the way of producing energy, which among other factors, has a direct effect on the conservation of the natural environment and with a drag of the quality of life and health of the people. In the current decade has made great advances in the production of energy from clean, renewable sources, with the aim to reduce carbon footprint, the emission of greenhouse gases, in addition to having a schema generation more efficient and less expensive in the long term, giving way to a sustainability over time and a sustainability in the present. For human beings to have access to energy has a direct and indirect in their quality of life, as it is able to re-evaluate the use of natural resources for everyday activities such as lighting, cooking food with firewood, among others. In addition, on the general level people feel more comfortable and at ease, at the same time that their level of resilience grows.